2002
DOI: 10.1016/s1010-7940(02)00585-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved early results after heart valve surgery over the last decade

Abstract: It is confirmed that early risks for death after heart valve surgery have decreased. This improvement was consistent after adjustment for risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…The comparison between the findings of our analysis and those from Hellgren et al [24] confirms emergency surgery, high age and class IV heart failure as predictors of higher operative risk. From these findings, we concluded that intervention in these factors -either by changing the criteria for surgical recommendation (making the decisions earlier), by creating better clinical protocol, or by changing operative routines -will allow us to achieve better results in terms of reducing surgical mortality and hospital expenses.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The comparison between the findings of our analysis and those from Hellgren et al [24] confirms emergency surgery, high age and class IV heart failure as predictors of higher operative risk. From these findings, we concluded that intervention in these factors -either by changing the criteria for surgical recommendation (making the decisions earlier), by creating better clinical protocol, or by changing operative routines -will allow us to achieve better results in terms of reducing surgical mortality and hospital expenses.…”
Section: Discussionsupporting
confidence: 81%
“…Hellgren et al [24] correlated the higher morbidity and mortality in heart valve replacement surgery in patients older than 70 years (OR=2.1), IV NYHA functional class (OR=2.2), preoperative cardiac arrest (OR of 3.5) and an aortic clamping time of more than 150 minutes (OR of 3.2). Atrial fibrillation was a significant operative risk factor when considered the type of valve procedure; in aortic or mitral-aortic replacements, it represented a risk factor with an OR of 4.1, but showed no relative influence on mitral replacements.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The frequency of double-valve surgery (DVS; concomitant mitral [MV] and aortic [AV] valve surgery) remains low (3% to 14%) compared with isolated valve surgery for aortic and mitral pathologies. [3][4][5] For these patients, surgery remains the sole and definitive treatment for relieving symptoms and extending life. Studies involving concomitant AV and MV surgery are limited compared with those for isolated AV and MV surgery.…”
mentioning
confidence: 99%
“…[3][4][5] Astor et al 6 reported an in-hospital odds ratio for mortality of 1.75 (PϽ0.001) in patients having DVS. Several studies have documented increased in-hospital mortality in older patients undergoing DVS.…”
mentioning
confidence: 99%
“…are being considered for surgery, due to their tendency to intervene earlier in the disease state, reflecting lower prevalence / intensity of recognized risk factors and, thus, resulting in lower hospital mortality [19]. But if some of the demographic or operative characteristics, which in the past increased surgical mortality and morbidity, can now have its influence minimized, and surgical indication progressively increased of older patients (and with more comorbidities) in different surgical series, can also induce changes in the profile of patients considered for valve surgery [20].…”
Section: Fig 1-risk Factors For Hospital Mortality With Expression mentioning
confidence: 99%